Upaya Guru Pendidikan Agama Kristen Menanamkan Indikator Komitmen Kebangsaan dan Indikator Anti Kekerasan dalam Moderasi Beragama di Kelas X SMKN 1 Palangka Raya - Ullo, Glen; Rahmelia, Silvia; Wirawan, Aprianto (Lembaga Penelitian dan Pengabdian pada Masyarakat Institut Agama Hindu Negeri Tampung Penyang Palangka Raya, 2025)
Abstract The results of this research describe that: (1) The efforts of Christian Religious Education teachers are to foster, guide and supervise students implementing indicators of national commitment in living a life of religious moderation in the SMKN 1 Palangka Raya environment. Teachers develop students through topics discussed about life in a pluralistic society which are related to indicators of national commitment. Apart from developing teachers, they also guide and supervise students in carrying out national commitments within the SMKN 1 Palangka Raya environment. (2) The Christian Religious Education teacher's efforts are to develop, guide and supervise students implementing anti-violence indicators within the SMKN 1 Palangka Raya environment. The teacher provides guidance that is taught through the topics of the principles of loyalty, justice and love. Teachers also guide and supervise students' behavior at school, apart from that, religious teachers have first practiced non-violence.